Lazy model generation for improving the efficiency of forward reasoning theorem provers - Hasegawa, Ryuzo; Koshimura, Miyuki; Fujita, Hiroshi (1992)
Abstract: "This paper presents several algorithms for implementing efficient theorem provers based on lazy model generation. The tasks of the model generation based prover are the generation and testing of atoms which are to be the elements of a model for the given theorem. A problem with this method is explosion in the number of generated atoms and in the computational cost in time and space consumed by the generation processes. The lazy model generation method avoids generating unnecessary atoms that are irrelevant to obtaining proofs. Indeed, no matter what calculus a prover may take, any theorem which inherently has a large search space cannot be solved with the limited resources available under normal circumstances, unless the generation and retention of information is carefully managed. The lazy model generation method provides flexible control for efficient use of resources in simple manner, thereby decreasing the time and space complexity of some algorithms by several orders of magnitude."
Keywords: Automatic theorem proving